Effect of oral processing on texture, rheology properties, and microstructure of three rice varieties. (30th November 2021) - Asimi, Sailimuhan; Xin, Ren; Min, Zhang; Dongxiao, Liu; Sohail, Amjad; Meng, Li; Jie, Peng; Zhenhua, Wang; Shan, Liang; Ziyuan, Wang
Abstract: The differences of physical properties of cooked rice among different mastication processes were studied in three rice cultivars differing in amylose contents, that is, japonica rice (JR), indica rice (IR), and waxy rice (WR). The results indicated that the average amount of saliva added was 303.4 ± 15.9 mg/g for JR, 351.5 ± 16.1 mg/g for IR, and 299.1 ± 13.5 mg/g for WR during oral processing. The proportion of free water in JR significantly increased ( p < .05), whereas the proportion of weak bound water significantly decreased ( p < .05). With the progress of mastication, the apparent viscosity of cooked rice decreased, and the elastic modulus G′ decreased more than the viscous modulus G″ . In addition, small boluses were mostly produced in the early stage of oral processing. The proportion of small particles of JR and IR increased with extended mastication, but no significant change in that of WR. The hardness of bolus also significantly decreased ( p < .05) in the early stage of mastication. With the progress of mastication, the cohesiveness of JR rice boluses increased significantly ( p < .05). At the swallowing point, the cohesiveness were 0.23 ± 0.03 for JR, 0.25 ± 0.02 for IR, and 0.32 ± 0.05 for WR, respectively. Saliva secretion and mastication allowed cooked rice to be swallowed by decreasing its hardness and apparent viscosity, increasing its cohesiveness, water content, and proportion of small particles. Practical applications: This article investigated the changes of physical properties of three varieties of cooked rice during oral processing. Abstract :